2012
DOI: 10.1002/sys.21241
|View full text |Cite
|
Sign up to set email alerts
|

Using model‐based systems engineering as a framework for improving test and evaluation activities

Abstract: Model‐based systems engineering (MBSE) approaches are based on a paradigm shift from document‐centric engineering to model‐based engineering. Although MBSE methods are intended to apply across the entire system life cycle, one area that has not received much attention to date is the role of test and evaluation. Test and evaluation activities provide information that reduces the uncertainty about system performance, effectiveness, and suitability. This uncertainty reduction becomes particularly important within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Another interesting topic for discussion is whether to integrate such a simulation study into an overall MBSE framework and in what manner. Bjorkman et al 17 already showed that it can be valuable to couple testing procedures to simulation studies, to gain mutual benefits. The Design Framework 22 advocates that it is important to capture design rationale throughout the various lifecycle phases.…”
Section: Discussionmentioning
confidence: 97%
“…Another interesting topic for discussion is whether to integrate such a simulation study into an overall MBSE framework and in what manner. Bjorkman et al 17 already showed that it can be valuable to couple testing procedures to simulation studies, to gain mutual benefits. The Design Framework 22 advocates that it is important to capture design rationale throughout the various lifecycle phases.…”
Section: Discussionmentioning
confidence: 97%
“…In the MBSE approach, SE activities are shown by use of model of diagrams and hierarchies. Also, it depicts the system requirements, functions, design, as well as verification and test information (Bjorkman, Sarkani, & Mazzuchi, 2013).…”
Section: Theorymentioning
confidence: 99%
“…Even so, MBSE presents an attractive option that, when implemented correctly, has great value. Numerous studies have attested to the utility and applicability of MBSE to various engineering disciplines, including space systems, information security systems, and test and evaluation . MBSE has been shown to have explicit methods for most design actions, allowing it to serve effectively in an integration role with demonstrated payoffs in supporting conceptual and creative design problems .…”
Section: Introductionmentioning
confidence: 99%